2016
DOI: 10.1007/s00330-016-4306-6
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue and muscle attenuation as novel biomarkers predicting mortality in patients with extremity sarcomas

Abstract: • CT-attenuation of adipose tissue and muscle predict mortality in sarcoma patients • CT-attenuation predicts mortality independent of established prognostic factors • Patients with sarcomas often undergo CT for staging or surveillance • Adipose tissue and muscle attenuation could serve as biomarkers for mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 40 publications
7
77
0
Order By: Relevance
“…In a previous study having patients with colon cancer, only the VAT parameters had significant clinical values . In other previous studies with non‐small cell lung cancer, extremity sarcoma, and prostate cancer, only the SAT parameters were significantly associated with clinical outcomes . Considering these results of the previous studies, VAT and SAT could have different characteristics and could be related to tumor cells with different mechanisms according to the type of cancer.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…In a previous study having patients with colon cancer, only the VAT parameters had significant clinical values . In other previous studies with non‐small cell lung cancer, extremity sarcoma, and prostate cancer, only the SAT parameters were significantly associated with clinical outcomes . Considering these results of the previous studies, VAT and SAT could have different characteristics and could be related to tumor cells with different mechanisms according to the type of cancer.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, cancer cells can inversely affect adipocytes by dedifferentiating adipocytes into fibroblast‐like cells, which increase the secretion of pro‐inflammatory cytokines and induce tumor cells to acquire more aggressiveness . In a previous study on nonhuman primates, increased attenuation of adipose tissue on noncontrast CT images corresponded to the inflammatory and fibrotic changes in adipose tissue, suggesting that the CT‐attenuation of adipose tissue can be used as an indicator of the qualitative changes of adipose tissue . Several studies have demonstrated the significant positive association between the CT‐attenuation of adipose tissue and prognosis in diverse diseases, including cardiovascular disease, extremity sarcoma, and prostate cancer .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations